Scopus-indexed Journals of Humanities & Social Science in Thailand Through Bibliometric Analysis - Maporn, Sattra; Puseerit, Jirarat (DESIDOC Journal of Library & Information Technology, 2024)
The research dissemination in the present day has been changed to the online era, and the analysis of academic journals holds significant importance in evaluating research output. This study focuses on Thai scopus-indexed journals in humanities and social sciences. The objective is to analyse outstanding research articles based on their citation counts and conduct a comprehensive bibliometric analysis using three selected journals. VOSviewer software was employed to explore the characteristics of these journals. The results reveal that the contributions in these journals encompass various areas such as education, agricultural production, business and economics, and social issues. Furthermore, the bibliometric analysis highlights the journals’ emphasis on research related to Thailand and nearby countries and shows the significant contributions made by Thai scholars. In conclusion, Thai scopus-indexed journals in the humanities and social sciences align with current research trends and exhibit collaborations from several continents and different areas. The findings of this study provide information for policymakers, journal publishers, and researchers to guide content strategies as well as promote collaboration among academia.